Preparation of a Strategic Plan in an Effort to Improve the Quality of Physics Learning at SMAN Depok - T.W., Alhidayatuddiniyah; Hidayat, Rais (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
The decline in the quality of Physics learning, which often fails to meet the learning outcomes that students are expected to achieve, has become a major problem. Based on this problem, this research aims to develop a strategic plan to improve the quality of Physics learning at SMAN Depok. The main focus of this research is identifying strategic needs in terms of developing teacher competency and optimising the use of technology in learning. The research method used is a qualitative descriptive method with a case study approach. Data collection was carried out through in-depth interviews with school principals, teachers and students. In addition, SWOT analysis is used to identify strengths, weaknesses, opportunities and threats that influence the quality of learning. The strategic plan is focused on increasing teacher competency, providing facilities, and using technology in learning. The results show that the main strength of SMAN Depok is the quality of teachers and adequate laboratory facilities, but the weakness lies in the lack of innovation in learning. Opportunities arise from government policy support through Merdeka Belajar, while threats come from competition from other, more innovative schools. The discussion recommends strategies for developing teacher competency, integrating learning technology, and external collaboration to improve learning. The research suggestion is regular evaluation and strengthening the use of digital technology in the teaching and learning process.